Posisi Kopi Robusta Indonesia di Pasar Jerman Menggunakan Metode Linear Approximate Almost Ideal Demand System - Sevi Oktafiana Fortunika; Harianto Harianto; Suharno Suharno (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2021)
Indonesia is one of the top coffee producers in the world. The major markets for Indonesian coffee are European Union (EU), then Germany is the largest importing country. This research analyzed the position for Indonesian robusta coffee in Germany among Vietnam and India as the major producers of robusta coffee as Indonesia. The econometric model of the Linear Approximate Almost Ideal Demand System was used to estimate a position for Indonesian robusta coffee among its competitors. The analysis utilized time-series data from 1996 to 2017. The results of the study showed that the main exporting countries, including Indonesia, tended to have lower import tariffs than other countries, not the main exporters. The demand for imported coffee beans was generally influenced by the prices of major exporters, but demand for imported roasted coffee was not affected by the prices of major importing countries. Indonesian coffee beans in the German market was elastic, while roasted coffee was inelastic. Indonesian coffee competed with Vietnam both for coffee beans and roasted coffee. The expenditure elasticity of Indonesian coffee beans was positive and Indonesian roasted coffee was negative.